DIGITAL TRANSFORMATION OF VILLAGE ADMINISTRATION IN ENHANCING COMMUNITY PARTICIPATION, TRANSPARENCY, AND SERVICE EFFICIENCY: A QUALITATIVE STUDY IN HARAPAN VILLAGE USING NVIVO - Marsuki; Aidah. S (P3M Stia Al Gazali Barru and Meraja media, 2026)
[Full Paper] to pdf Copyright (c) 2026 Meraja journal